The problem of an object evaluation and optimization under several criteria - Voronin, A.; Savchenko, A. (Проблеми керування та інформатики, 2023)
The problems of estimation and optimization of an object pursuing several goals are considered. Розглянуто задачі оцінки та оптимізації об'єкта, що переслідує кілька цілей.